An Application of STWS Technique in Solving Stiff Non-linear System: 'High Irradiance Responses' (HIRES) of Photomorphogenesis - Dhayabaran*, A. Emimal Kanaga Pushpam and D. Paul (Recent Research in Science and Technology, 2011)
This paper illustrates an application of the Single Term Walsh Series (STWS) technique in solving stiff non-linear system: ‘High Irradiance RESponses’ (HIRES) of Photomorphogenesis from plant physiology. The chemical reaction scheme of HIRES problem has been modelled into system of stiff non-linear differential equations. This stiff system has been solved using the STWS technique. The STWS solutions are compared with the results obtained by the well-known solvers, namely, VODE and RADAU5. The applicability of the STWS technique has been tested.